Clinical outcomes of adverse drug reaction-related hospital admissions in older adults with diabetes - Vonna, Azizah; Salahudeen, Mohammed S.; Peterson, Gregory M. (Frontiers in Pharmacology, 2026)
AimThis is a retrospective cohort study aimed to investigate the association of adverse drug related (ADR)-related hospital admissions with adverse clinical outcomes, including in-hospital mortality, length of stay (LOS), and hospital readmission among older adults with diabetes.MethodsAll individuals aged 65 years and older with diabetes who were admitted to the three major public hospitals in Tasmania, Australia, between July 2017 and December 2023 were identified using International Classification of Diseases codes. Patients with at least one ADR-related hospital admission were propensity score matched with and those without ADR-related admissions based on age, sex, year of index admission, diagnosis-related groups, socioeconomic status, and comorbidities. Adjusted logistic regression was used to assess in-hospital mortality. Length of stay was analysed using a generalised linear model with a Gamma distribution, and readmission risk at 30, 60, and 90 days was assessed using Cox proportional hazards models.ResultsAfter matching, a total of 5,038 older patients with diabetes were included in the in-hospital mortality analysis, and 4,674 were included in the LOS and readmission analyses. Patients with ADR-related hospitalisations had a significantly higher risk of in-hospital mortality (adjusted odds ratio = 1.31; 95% CI: 1.03–1.66; p < 0.05), longer LOS (adjusted ratio = 1.24 (1.13–1.37); p < 0.001, and a greater risk of readmission (the highest adjusted hazard ratio was at 60 days = 1.29 (1.14–1.45); p < 0.001) compared to those without ADR-related hospital admissions.ConclusionADR-related hospital admissions were associated with poorer clinical outcomes in older adults with diabetes, including greater mortality, prolonged hospital stays, and increased risk of readmission. These findings underscore the importance of early ADR detection, structured medication review, ongoing monitoring, and patient-centered education to improve medication safety and optimise outcomes in this high-risk group.